The Concept of Morality-Based Education in Q.S Al-Hujurat: 11-13 with a Comparison of the Interpretations of Ibn Katsir and Al-Misbah - Asysyifa, Zulaikhah Itsnan; Mustofa, Triono Ali (Universitas Islam Negeri Sumatera Utara, 2025)
In this era of industrial revolution, there has been a shift in behavior that deviates from the moral values taught in Islam. This situation reflects a moral crisis and decline in morality, largely triggered by the rapid pace of globalization and the development of information technology. Moral education is the appropriate foundation for preventing moral deviation. The Qur'an and Hadith serve as the benchmarks for obtaining knowledge in moral education. This study aims to compare the interpretations of Ibn Kathir and Al-Misbah to provide an in-depth analysis of the ideas regarding moral teachings in QS. Al-Hujurat verses 11-13. A qualitative approach and literature review research techniques are combined in this study. Content analysis is the data analysis method used. The Tahlili interpretive approach is employed for data analysis. Comparative analysis is the data analysis method used in this study. The results of this study indicate that QS. Al-Hujurat: 11-13 contains basic moral education principles for humans, namely respecting and honoring others, avoiding mockery, having good intentions, and not gossiping. These are basic moral education principles and can be applied to fellow Muslims or people of other faiths. Universally, this verse emphasizes the importance of guarding one's speech and actions toward everyone.